Clinical procedures, designs, and survival rates of all-ceramic resin-bonded fixed dental prostheses in the anterior region: A systematic review - EVREN, BUKET; YILDIZ, COŞKUN; TEZULAŞ, EMRE; ÖZKAN, YASEMİN (WILEY, 2018)
Objectives: The aim of this study is to systematically review all the clinical articles about all-ceramic resin-bonded fixed dental prosthesis (RBFDP) in the anterior region and assess their designs, clinical procedures, and survival rates. A systematic review was conducted after searching electronic databases PubMed/Medline and EBSCOhost Research Databases for articles published in English between 1987 and July 2017. Materials and Methods: The inclusion criteria were selected as all clinical studies, original design clinical reports, and clinical reports (follow-up time more than 1 year) as all clinical information in the literature are desired to be included in the present review. Results: The initial electronic search generated 472 articles from PubMed/Medline and 464 articles from EBSCOhost Research Databases. After selection of the articles as per the inclusion criteria, a final sample of 29 original studies is decided as: 1 randomized controlled clinical trial, 4 clinical controlled trials, 4 prospective cohort studies, 2 retrospective cohort studies, 6 original design clinical reports, and 12 clinical reports. After evaluation of the selected articles, it is likely that cantilever design all-ceramic RBFDPs are more successful than two retainer design in the anterior region; however, there is limited evidence for this result in the literature. Conclusion: Well-designed randomized controlled clinical trials with large sample size are still needed to achieve more accurate results about the clinical success rate of different RBFDPs designs in the anterior region.
Keywords: adhesive bridges; resin-bonded fixed dental prostheses; PARTIAL DENTURE; LATERAL INCISORS; REPLACEMENT; SURFACE; PERIOD